Untargeted Elemental and Metabolomic Profiling of Some Poaceae Species Using LIBS and GC-MS Methods. Issue 9 (15th May 2021) - Fatima, Iram; Hussain, Tanveer; Rafay, Muhammad; Kanwal, Sobia; Rauf, Naseem; Malik, Tahir S. S.; Mahmood, Tariq
ABSTRACT: Grasses are an underestimated repository of unique medicinal properties on the planet. Present study was designed to ascertain compositional analysis of ten Poaceae species via laser-induced breakdown spectroscopy and gas chromatography–mass spectrometry (GC-MS) methods. LIBS spectra showed the presence of Na, Mg, K, Ca, and Fe nutritional elements and Al, Ti, Sr, Ba, Si, Al, Ar, Cs, and Li toxic elements. The intensity of most of the elements was high in I. cylindrica, D. annulatum, S. halepense, E. indica, and O. compressa . GC-MS analysis revealed the existence of almost 70 different compounds including aldehydes, fatty acids, phenols, monoterpenoids, and hydrocarbons eluted at different retention times. Among these, m-cresol, 1, 4-dimethylnaphthalene, 1-pentadecene, 2, 2ˈ, 5, 5ˈ-tetramethyl-1, 1ˈ-biphenyl, 1-heptadecene, hexadecanoic acid-methyl ester, and fluoranthene were detected in all species in varying concentrations. All-inclusive, hexadecanoic acid was found as a major component (20–30%) in most of the species. Data of this study suggest that these species are a valuable source of elements and compounds that can be utilized in foods as well as in preparing drugs for treating various ailments. In the end, the biological significance of the observed compounds has been reported. Perhaps, this is the first study on the selected grasses using LIBS and GC-MS techniques.